Relation of renal cortical gluconeogenesis, glutamate content, and production of ammonia - Pagliara, Anthony S. (1970)
Glutamate is an inhibitor of phosphate dependent glutaminase (PDG), and renal cortical glutamate is decreased in metabolic acidosis. It has been postulated previously that the rise in renal production of ammonia from glutamine in metabolic acidosis is due primarily to activation of cortical PDG as a consequence of the fall in glutamate. The decrease in cortical glutamate has been attributed to the increase in the capacity of cortex to convert glutamate to glucose in acidosis. In the present study, administration of ammonium chloride to rats in an amount inadequate to decrease cortical glutamate increased the capacity of cortex to produce ammonia from glutamine in vitro and increased cortical PDG. Similarly, cortex from potassium-depleted rats had an increased capacity to produce ammonia and an increase in PDG, but glutamate content was normal. The glutamate content of cortical slices incubated at pH 7.1 was decreased, and that at 7.7 was increased, compared to slices incubated at 7.4, yet ammonia production was the same at all three pH levels. These observations suggest that cortical glutamate concentration is not the major determinant of ammonia production. In potassium-depleted rats there was a 90% increase in the capacity of cortex to convert glutamate to glucose, yet cortical glutamate was not decreased. In vitro, calcium more than doubled conversion of glutamate to glucose by cortical slices without affecting the glutamate content of the slices, and theophylline suppressed conversion of glutamate to glucose yet decreased glutamate content. These observations indicate that the rate of cortical gluconeogenesis is not the sole determinant of cortical glutamate concentration. The increase in cortical gluconeogenesis in acidosis and potassium depletion probably is not the primary cause of the increase in ammonia production in these states, but the rise in gluconeogenesis may contribute importantly to the maintenance of increased ammoniagenesis by accelerating removal of the products of glutamine degradation.